AN ECOFEMINIST READING OF P.VALSALA’S SHORT STORIES, “TREE AND MAN” AND “THE WILD DUCKS OF THE PEAK” - E.Krishnan Namboothiri (JOURNAL OF ENGLISH LANGUAGE AND LITERATURE, 2018)
Discourse and discussion on environment attain great significance at present as the planet Earth itself has become an endangered one. The attitude of human beings to nature over centuries has resulted in the severe ecological crisis for which no solution has been formulated so far. Materialism and lack of spiritual values have reduced Nature to the level of a mere commodity to be marketed. Ecology as a major stream of thought found space in academic and literary discussions in the Western world with the publication of Silent Spring (1962) by Rachael Carson. The fact that Ecological discussions started there with initiative of a woman attains great significance in ecofeminism. Women also have been treated as a commodity and become victims of exploitation in the society. The suffering and struggle for survival of Nature and Women are more or less same. The article focuses on issues pertinent to ecology and women. Two short stories, “Tree and Man” and “The Wild Ducks of the Peak”, by a Malayalam writer, P.Valsala, have been taken up for discussion here. Malayalam is the regional language of Kerala, a southern state in India and P.Valsala is a contemporary popular and prolific writer in Malalayalam literature.